Analisis Kinerja Pemasaran Digital Berbasis KPI. Studi Kasus Pada UMKM Destinasi Wisata Ekonomi Kreatif Situ Gede Kota Bogor - Kurniawan Widagdyo (Bisnis Event, 2026)
The development of the Situ Gede tourism area in Bogor City as a creative economy-based destination is part of the implementation of regional tourism development policies outlined in the 2022 Regional Tourism Development Master Plan (RIPPARDA). This area holds significant potential in strengthening Bogor City's image as a creative city that emphasizes community empowerment and environmental sustainability. One of the key elements in this development is the presence of Micro, Small, and Medium Enterprises (MSMEs), which have grown organically and play an important role in enhancing the attractiveness of the destination. This study aims to analyze the level of KPI-based digital marketing utilization among MSMEs in the Situ Gede area. The research employs a descriptive qualitative approach through field observations and in-depth interviews. The findings indicate that, out of 11 active MSMEs, the level of digital marketing adoption is categorized as moderate, with social media being the dominant promotional tool. However, performance indicators such as engagement rate, content consistency, and the utilization of Search Engine Optimization (SEO) and geo-tagging remain relatively low. The results highlight the need for continuous assistance and capacity building for MSME actors in optimizing digital marketing strategies, including the use of SEO, Social Media Optimization (SMO), and marketplace platforms to enhance marketing effectiveness and competitiveness. These efforts are expected to improve MSME performance while strengthening the creative economy-based tourism ecosystem in Situ Gede.